CARACTERIZACIÓN DEL CRECIMIENTO DE DOS ESPECIES DE SOTOL (Dasylirion /eiophyl/um Engelm. ex Trelease y D. se!eke Bogler) FERTILIZADAS CON NITROGENO Y FÓSFORO - Vega Cruz, Jorge; Melgoza Castillo, Alicia; Sierra Tristán, J. Santos (Revista Mexicana de Ciencias Forestales, 2020)
Dasylirion /eiophy/lum and D. sereke (Nolinaceae) from Chihuahua state are important in the liquor industry and, consequently, are subject to an intense exploitation, thus, it is necessary to generate techniques that favour its nursery propagation in order to establish plantations. The purpose of this study was to determine the effect of the diaspore pericarp over germination and emergence, as well as of fertilization on the seedling stage, Seeds were collected from two places in the State; germination was assessed in laboratory over a paper layer and the dyaspore emergence from the ground with and without the pericarp. Four nitrogen and three phodphorous levels were used. When the wing pericarp was removed, germination in both species was higher than 80 percent in the laboratory and around 30 percent in the soil, anq without the removal of seed covers, emergence was lower than 2 percent. Ouring the first five months there was no response to fertilizing doses. D. leiophy/lum plants showed higher phytomass production but was even lower than 0.05 g. lnteraction was confirmed between fertilization and the species in the relative growth rate; even though differences were lower than 11 mg d·1 in both taxa, it has no practica! relevance. The green part : root proportion was 20.5 : 26.5 for Dasylirion leiophyllum and 18.6: 25.2 cm for D. sereke.